Morbidities among babies of diabetic mothers with variable maternal glycemic control - Zahrah Jamal Hamad; Abbas Abdulkadir Rabaty (Advanced Medical Journal)
Background and objectives:Diabetes in pregnancy is associated with an increased risk of complications in both the mother and the fetus. Early diagnosis by screening of pregnant women between 24 to 28 weeks of gestation with proper control of diabetes is essential to reduce these adverse neonatal outcomes. This study aims to determine mor- bidities in infants of diabetic mothers with variable maternal glycemic state in comparison to infants of non-diabetic mothers.